2008
DOI: 10.1111/j.1365-3091.2008.00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional modelling and sequence stratigraphy of a carbonate ramp‐to‐shelf transition, Permian Upper San Andres Formation

Abstract: This study highlights three‐dimensional variability of stratigraphic geometries in the ramp crest to basin of mixed carbonate–siliciclastic clinoforms in the Permian San Andres Formation. Standard field techniques and mapping using ground‐based lidar reveal a high degree of architectural complexity in channellized, scoured and mounded outer ramp stratigraphy. Development of these features was a function of location along the ramp profile and fluctuations in relative sea‐level. Deposition of coarse‐grained and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…In the Permian Basin of west Texas, bypass of eolian sand into downslope environments is well documented (Phelps et al, 2008). Sequence boundaries sit directly below packages of siliciclastics, suggesting that Khufai sands also may have accumulated during increases in accommodation.…”
Section: Clastic Inputmentioning
confidence: 98%
See 2 more Smart Citations
“…In the Permian Basin of west Texas, bypass of eolian sand into downslope environments is well documented (Phelps et al, 2008). Sequence boundaries sit directly below packages of siliciclastics, suggesting that Khufai sands also may have accumulated during increases in accommodation.…”
Section: Clastic Inputmentioning
confidence: 98%
“…Previous studies of mixed clastic-carbonate systems have demonstrated the stratigraphic controls on sand-body accumulation (Kerans et al, 1994;McNeill et al, 2004;Barnaby and Ward, 2007;Phelps et al, 2008). In the Permian Basin of west Texas, bypass of eolian sand into downslope environments is well documented (Phelps et al, 2008).…”
Section: Clastic Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations can also be done directly on the DOM. This usually implies manual picking of XYZ points on the model in order to derive, for example, layering and platform geometry (Boro, 2012;Gramigna et al, 2013), faults, fractures, and slip vectors (Jones et al, 2009;Kurtzman et al, 2009;Rotevatn et al, 2009;Lapponi et al, 2011;Jacquemyn et al, 2012), vugs and karst cavities (Kurtzman et al, 2009;Labraña, 2011) or the geometry and distribution of sedimentary (Phelps et al, 2008;Fabuel-Perez et al, 2009) and diagenetic geobodies . Several successful attempts are made for automated processing.…”
Section: Study Aims and Context Of Digital Outcrop Characterizationmentioning
confidence: 99%
“…The use of digital field techniques is becoming a more common tool to aid fieldwork and some powerful applications have been demonstrated in recent studies, for example in sedimentological and structural studies (Hodgetts et al 2004;Verwer et al 2004b;Adams et al 2005;Labourdette and Jones 2007;Phelps and Kerans 2007;Olariu et al 2008;Phelps et al 2008;Fabuel-Perez et al 2009a;Hodgetts 2009;Verwer et al 2009a;Verwer et al 2009b;Wilson et al 2009) as well as in earth surface process (Wawrzyniec et al 2007;McCormick et al 2008) and ichnology (Bates et al 2008). Work has further focussed on how the digital data can best be captured and visualized, and in quantifying uncertainties inherent in the datasets (Bond et al 2007;Enge et al 2007;Verwer et al 2007;Buckley et al 2008).…”
Section: Introductionmentioning
confidence: 98%